Molecular phylogenetic analysis of the catfish species Auchenoglanis occidentalis (Valenciennes, 1840) (Pisces: Claroteidae) from Lake Turkana in East Africa: taxonomic implications - Okwiri, Brian; Cao, Liang; Nyingi, Dorothy Wanja; Zhang, E. (Zootaxa, 2018)
Cytochrome c oxidase subunit I (COI) gene sequences of two specimens here recognized as Auchenoglanis occidentalis from Lake Turkana in the Ethiopian section were determined. A COI gene-based phylogenetic analysis was performed for these along with sequences of African catfish species from the family Clarotidae available in GenBank. Based on results of this analysis, it is concluded that (1) the currently identified A. occidentalis is a species complex that includes several distinct species; (2) the Niger River basin harbors two distinct species of Auchenoglanis, one of which occurs in Lake Turkana, as well as A. biscutatus; and (3) A. sacchii is likely a valid species, but it is not the endemic species of Lake Turkana. It is suggested here that species diversity of Auchenoglanis requires further study based on molecular and morphological evidence.